Produksi Tanaman Cabai Rawit Pada Pola Lanskap Agroforestri Tanaman Karet - Yulius Budi Prastiyo; Alvera Prihatini Dewi Nazari; Hadi Pranoto; Monika Agustia; Muh. Dzulkifly Ashan; Susi Indriani (Jurnal Lanskap Indonesia, 2023)
The application of agroforestry landscape pattern for rubber plant with cayenne pepper plant has an effect on productivity and land use level compared to monoculture system. This reaserch aims to obtain data on the production of cayenne pepper plants in rubber plants agroforestry system and compare it with monoculture systems. The research was located in Sumber Sari Village, Sebulu District, Kutai Kartanegara Regency with two planting system treatments (P), it’s monoculture system planting (p1) and rubber plants agroforestry system (p2) with 6 plots as replicates each. The variables measured were the production of cayenne pepper plants until the 5th (fifth) harvest based on the average sample. Data were analyzed using the Independent Sample t-test with a significant level (α) of 5%. Production of cayenne pepper plants in rubber plants agroforestry system reached 2.32 Mg.ha-1 which was greater than monoculture system with a production of 1.46 Mg.ha-1 with F-Count 1.74 and F- Table 7.15. This is due to the growth environmental conditions and photosynthetic efficiency, with a higher daily temperature of 300C in monoculture system, it will slow down of photosynthesis and accelerate respiration rate, whereas the daily temperature in an agroforestry planting system with rubber plants is only 260C, so that the photosynthesis rate is higher than respiration rate, because the optimum temperature for cayenne pepper plants photosynthetic is 21-270C. Cayenne pepper plants in agroforestry landscape pattern for rubber plant were able to produce better yields than monoculture planting systems based on two average similarity test.